Constructing a talent identification index system and evaluation model for cross-country skiers - Huang, X.; Wang, G.; Chen, C.; Liu, J.; Kristiansen, B.; Hohmann, A.; Zhao, K. (Journal of Sports Sciences, 2021)
A talent identification index system for male and female cross-country skiers in four age groups (11-12 years old, 13-14 years old, 15-16 years old, and 17-18 years old) was established. The system comprises five body shape indexes (i=5): Leg-to-Body Ratio (LBR), body fat percentage, maturity status, spreaded brachia index, and upper extremity length. The physiological function indexes (i=2) are VO2max and haemoglobin mass (Hb). The psychological indexes (i=5) cover reaction time, perception speed, a quality-of-will scale, an attention test, and operational thinking. The physical fitness indexes (i=11) comprise upper limb explosiveness, vertical jump, 3000-metre run, orthostatic forward flexion, closed-eyes single-leg stand, standing long jump, 20-metre sprint, pull-ups (males), flexed arm hang (females), hexagon jump, and a Functional Movement Screen (FMS) test. The athletic performance indexes (i=3) comprise on-snow time trials for 1.2 km, 5 km, and 10 km. The talent identification evaluation model was created using automated evaluation software. The talent identification index system and evaluation standard table for cross-country skiers passed the P60 shortlist and P90 elite boundaries established using the percentile method. Thus, the results of this test profile verify that the evaluative model is objectively effective.